PHD-2 Suppression in Mesenchymal Stromal Cells Enhances Wound Healing. Issue 1 (January 2018) - Ko, Sae Hee; Nauta, Allison C.; Morrison, Shane D.; Hu, Michael S.; Zimmermann, Andrew S.; Chung, Michael T.; Glotzbach, Jason P.; Wong, Victor W.; Walmsley, Graham G.; Peter Lorenz, H.; Chan, Denise A.; Gurtner, Geoffrey C.; et al.
Abstract : Background: Cell therapy with mesenchymal stromal cells is a promising strategy for tissue repair. Restoration of blood flow to ischemic tissues is a key step in wound repair, and mesenchymal stromal cells have been shown to be proangiogenic. Angiogenesis is critically regulated by the hypoxia-inducible factor (HIF) superfamily, consisting of transcription factors targeted for degradation by prolyl hydroxylase domain (PHD)-2. The aim of this study was to enhance the proangiogenic capability of mesenchymal stromal cells and to use these modified cells to promote wound healing. Methods: Mesenchymal stromal cells harvested from mouse bone marrow were transduced with short hairpin RNA (shRNA) against PHD-2; control cells were transduced with scrambled shRNA (shScramble) construct. Gene expression quantification, human umbilical vein endothelial cell tube formation assays, and wound healing assays were used to assess the effect of PHD knockdown mesenchymal stromal cells on wound healing dynamics. Results: PHD-2 knockdown mesenchymal stromal cells overexpressed HIF-1α and multiple angiogenic factors compared to control ( p < 0.05). Human umbilical vein endothelial cells treated with conditioned medium from PHD-2 knockdown mesenchymal stromal cells exhibited increased formation of capillary-like structures and enhanced migration compared with human umbilical vein endothelial cells treated with conditioned medium from shScramble-transduced mesenchymal stromal cells ( p < 0.05). Wounds treated with PHD-2 knockdown mesenchymal stromal cells healed at a significantly accelerated rate compared with wounds treated with shScramble mesenchymal stromal cells ( p < 0.05). Histologic studies revealed increased blood vessel density and increased cellularity in the wounds treated with PHD-2 knockdown mesenchymal stromal cells ( p < 0.05). Conclusions: Silencing PHD-2 in mesenchymal stromal cells augments their proangiogenic potential in wound healing therapy. This effect appears to be mediated by overexpression of HIF family transcription factors and up-regulation of multiple downstream angiogenic factors. Abstract : Supplemental Digital Content is available in the text.